Réactions et résilience des populations face à la crue de 2012 dans le cinquième arrondissement de Niamey - Adam Abdou Alou; Céline Lutoff; Harouna Mounkaila (VertigO)
This study focuses on the way in which authorities and populations deal with flooding phenomena. The fifth municipality of Niamey city has been threatened since 2012.This situation impacts on economy of its population. The aim of this article is to understand the logics of each of these actors in implemented strategies at the time and following the event. Combining qualitative and quantitative approaches, the study made it possible to highlight several measures developed by authorities and individuals to deal with the events. In response to the 2012 phenomena and the dysfunctions observed in terms of warning and population evacuation, prevention and protection strategies including enhancement of protective dike along the river as well as the relocation of the most exposed populations and prohibition of construction in flood zones have been initiated by the authorities. These measures have been complemented by various individual self-protection strategies using local materials in water-resistant housing reconstruction.